Functional analysis : applications in mechanics and inverse problems - Lebedev, L. P. (Solid mechanics and its applications, 2002)
This is a book for people who want to use functional analysis to justify approximate methods in mechanics and inverse problems. It provides such researchers with the tools they need without having to assimilate or skip through concepts they do not need.